Formation of state’s rights to self-defense - Широкова-Мурараш, Ольга Геннадіївна; Надашковська, Євгенія Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article examines the problem of evolutionary development institution of the state to defend itself, becoming a modern content of this institution, analyzing relevant scientific thought, and nominated andconfirmed that the right of self-defense is one of the fundamental institutions of modern international law, primarily because the most common reason of using force by States is the realization of their right to selfdefense.